2013
DOI: 10.5812/hepatmon.11038
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Chronic Hepatitis C Treatment Regimen: First Report From a Referral Center in Iran

Abstract: BackgroundVarious aspects of adherence to HCV treatment such as frequency, risk factors as well as causes of non-adherence, and its real role in clinical and virological outcome of the infected patients have remained largely unknown.ObjectivesThe current study aimed to evaluate patients’ adherence to anti-HCV medications in Iran.Materials and MethodsFrom October 2010 to March 2011, socio-demographic characteristics, features of HCV infection, clinical properties, and habitual history of 190 patients were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…[ 22 24 30 31 32 33 ] Overestimation is a limitation of this method and reliability of the self-reporting questionnaire closely depends on the level of literacy and the cognitive ability of individuals. [ 34 ] Despite these issues, a meta-analysis of 65 studies has demonstrated that self-reporting is a valid method for assessing the adherence to antiretroviral medications. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 24 30 31 32 33 ] Overestimation is a limitation of this method and reliability of the self-reporting questionnaire closely depends on the level of literacy and the cognitive ability of individuals. [ 34 ] Despite these issues, a meta-analysis of 65 studies has demonstrated that self-reporting is a valid method for assessing the adherence to antiretroviral medications. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Una revisión sistemática reciente sobre usuarios de drogas elegibles para el tratamiento del VHC con PEG-IFN y RBV mostró una RVS global del 56% (37% para genotipos 1/4 y 67% para 2/3) (Aspinall et al, 2013); estas cifras son algo inferiores a las de la mayoría de ensayos clínicos para estos fármacos, si bien son similares a las descritas en dos estudios de efectividad del tratamiento (39%-46% para genotipo 1 y 70%-84% para genotipo 2/3) (Borroni et al, 2008;Innes et al, 2012). En esta misma revisión sistemática (Aspinall et al, 2013) se observó una elevada adherencia al tratamiento, del 83%, algo superior a la mostrada en pacientes no usuarios de drogas (McHutchison et al, 2002;Ravi, Nasiri Toosi, Karimzadeh, Ahadi-Barzoki, y Khalili, 2013), si bien las diferencias observadas se explicarían por la propia definición de adherencia; además, la tasa de reinfección por VHC fue moderada (2.4 por 100p-a) sugiriendo que ésta tiene poco impacto en la efectividad del tratamiento a largo plazo (Aspinall et al, 2013).…”
Section: Situación Actual Del Tratamiento De La Hepatitis C En Pacienunclassified
“…These new treatments improve SVR rates significantly in difficult cases such as genotype 1 HCV infection 13 . Despite these advantages, in most of low-and middle income countries including Iran, access to these drugs is limited, mostly due to their high cost and unavailability 14 . Population based epidemiological studies have estimated that the prevalence of HCV in the Iranian general population is less than 0.5%, which is relatively low 15 .…”
Section: Introductionmentioning
confidence: 99%